If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 4(3x + -13) = -140 Reorder the terms: -4x + 4(-13 + 3x) = -140 -4x + (-13 * 4 + 3x * 4) = -140 -4x + (-52 + 12x) = -140 Reorder the terms: -52 + -4x + 12x = -140 Combine like terms: -4x + 12x = 8x -52 + 8x = -140 Solving -52 + 8x = -140 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '52' to each side of the equation. -52 + 52 + 8x = -140 + 52 Combine like terms: -52 + 52 = 0 0 + 8x = -140 + 52 8x = -140 + 52 Combine like terms: -140 + 52 = -88 8x = -88 Divide each side by '8'. x = -11 Simplifying x = -11
| 4x+8x+6x=24 | | -4(3-3m)=-37+7m | | 2(g-h)=b+y | | 9/7*-9/5 | | x^4-2x^3+14x^2-18x+45=0 | | 8k-k-5k+7-2k= | | -15+x+1=31 | | -4(2u-6)=-4-12u | | (6/5x)-(5/8)=(3/4x) | | -12-8(x-3)=-6(x-1) | | 6x-11x-12=-3(x-2) | | -(1+8X)=6-9X | | -9(10x+11)=351 | | 4-2y-y=2 | | tanx=(3/2)^(1/3) | | d=7+5x-8x | | 2x=1.8 | | 6-5x=9x-10x-6 | | 3x+7=8x-63 | | -12=-7–7/2s | | 14+7K=9K-2 | | -8(10x+3)=376 | | f(x)=4x^2-24x+31 | | 19v=-114 | | 3+4(x+6)=11 | | -9=2/3x–17 | | 8-4x=4-3(2x-6) | | 5(8v-8)=-6 | | 2x+3=-55 | | Y=1/2X-18 | | 65=5(5x-17) | | -2(x-3)=5(2x+13) |